Physical and chemical properties, structural characterization and nutritional analysis of kefir yoghurt - Xiao, Ran; Liu, Ming; Tian, Qing; Hui, Ming; Shi, Xin; Hou, Xiaoge (Frontiers in Microbiology, 2023)
Scanning electron microscopy (SEM), Confocal laser scanning microscopy (CLSM) and low field nuclear magnetic resonance (LF-NMR) were used to analyse the relationship between the chemical, texture, rheology, microstructure and water distribution of kefir (yeast, acetic acid bacteria and Lactobacillus plantarum) yoghurt fermented by mixed bacteria and L. plantarum L1 fermented yoghurt. This work was conducted to prepare a real champagne yoghurt and explore the difference between it and ordinary yoghurt. The nutritional evaluation of the two treatment groups was carried out by amino acid analysis, and the volatile flavour substances of the two treatment groups were detected by solid phase microextraction (SPME)–gas chromatograph (GC)–mass spectrometry (MS). Results showed that the addition of acetic acid bacteria and yeast increased the water content of kefir, resulting in a decrease in its water-holding rate. Moreover, the increase in acidity weakened the connection between the protein networks, the flocculent protein structure was not more densely stacked than the L1 group, and the internal bonds were unstable. The rheological results showed that the apparent viscosity decreased faster with the increase in shear force. The CLSM and LF-NMR showed that the hydration and degree of freedom of kefir yoghurt protein decreased, resulting in an increased protein network density. The SEM showed that the cross-linking between kefir casein clusters was considerably tight to form small chains, the pore distribution was uneven, and a weak cheese structure was formed. In addition, the volatile flavour substances in the kefir group increased the phenylethyl alcohol, isobutanol, and isoamyl alcohol compared with those in the L1 group, with a slight refreshing taste brought by alcohol and special soft malt alcohol aroma and rose aroma not found in ordinary yoghurt, which was more in line with the characteristics and taste of traditional kefir champagne yoghurt. Graphical Abstract